Input–output cost dynamics in farmers’ and agribusiness terms of trade, Indonesia livestock - Apedro, Henggi; Herliani (Politeknik Negeri Jember, 2026)
The livestock subsector is vital to Indonesia’s economy, supporting food security, employment, and rural livelihoods. Farmers’ terms of trade and agricultural business terms of trade are key welfare indicators, yet their short-run dynamics in the livestock subsector remain underexplored. This study examines short-run interactions and forecasts the dynamics of livestock farmers’ welfare and business conditions using a Vector Autoregressive (VAR) framework. Monthly data for 2019 to 2024, totaling 72 data were obtained from BPS (Badan Pusat Statistik)-Statistics. The analysis includes stationarity testing, lag selection, Granger causality, impulse response functions, variance decomposition, and one-year-ahead forecasting. The results indicate no long-run cointegration between the two indicators, implying the absence of a stable equilibrium relationship. However, strong short-run dynamics are observed: farmers’ terms of trade respond persistently to their own past values, while changes in agricultural business terms of trade exert negative and significant effects. Causality tests confirm a unidirectional relationship from agricultural business conditions to farmers’ welfare. Forecasts suggest modest improvements of about 2 to 3 percent in early 2025, which gradually taper later in the year. These findings suggest that stabilizing input costs is central to strengthening livestock farmers’ resilience.